The podcaster's audio handbook : a technical guide for creative people - Green, Corey Marie (Apress L.P., 2021)
"Podcasting is a powerful tool of communication and creative expression that doesn't need to be intimidating. This book brings together the creative and technical aspects of audio engineering to help podcasters communicate their ideas effectively and creatively. The Podcaster's Audio Handbook focuses on simple techniques that immediately elevate the audio quality of your podcast. The book provides an overview of podcast recording and editing techniques, so that podcasters can avoid common pitfalls. Readers will also gain access to audio downloads to enhance the learning process. With this book, you can improve the technical aspects of recording and editing your podcasts. Anyone can learn audio techniques and I encourage anyone to share their stories through podcasting. Unleash your creativity and connect with your audience!"--Back cover